2021
DOI: 10.3390/bs11070103
|View full text |Cite
|
Sign up to set email alerts
|

Comparison on Well-Being, Engagement and Perceived School Climate in Secondary School Students with Learning Difficulties and Specific Learning Disorders: An Exploratory Study

Abstract: Reading and writing skills influence the social status of students, exerting effects not only on learning, but also on wellbeing. This study aimed to assess the impact of diagnosis of specific learning disorder on well-being in secondary-school students, comparing students with a diagnosis of specific learning disorder (SLD-group), students showing learning difficulties without diagnosis (LD-group) and students without learning difficulties (control-group). Students were tested with neuropsychological screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 57 publications
0
4
1
Order By: Relevance
“…MAGs help students retain and construct resources (such as interest and motivation to learn) and a willingness to invest more psychological costs. However, the study also found that PAGs positively predict PSC, which is different from existing research [56]. A possible explanation is that PAGs make students lose internal personal resources, such as interest and motivation to learn, which requires external resources (e.g., a positive school climate) to intervene in the loss of these resources, such as reducing the difficulty of learning tasks to avoid students losing confidence in learning.…”
Section: The Chain Intermediation Of Perceived School Climate (Psc) A...contrasting
confidence: 92%
“…MAGs help students retain and construct resources (such as interest and motivation to learn) and a willingness to invest more psychological costs. However, the study also found that PAGs positively predict PSC, which is different from existing research [56]. A possible explanation is that PAGs make students lose internal personal resources, such as interest and motivation to learn, which requires external resources (e.g., a positive school climate) to intervene in the loss of these resources, such as reducing the difficulty of learning tasks to avoid students losing confidence in learning.…”
Section: The Chain Intermediation Of Perceived School Climate (Psc) A...contrasting
confidence: 92%
“…From a social and ecological perspective, schools can be considered as environments in which multifaceted interactions occur at the environmental, organizational and individual level [15], together with the effect of these different levels of interactions on individual and collective health and well-being. This is not surprising, since the impact of the school context on well-being is well recognized by recent literature [16][17][18]. In this vein, psychological well-being is understood and studied by adopting the positive psychology perspective, namely conditions and processes that contribute to the optimal functioning of individuals, groups, and institutions [19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, students with learning difficulties have been shown to be more sensitive to the supportiveness of adults at school than their peers (Lombardi et al, 2021). SWB.…”
Section: Schoolwork Difficultiesmentioning
confidence: 99%
“…On the other hand, support, which can be defined as providing psychological, special educational, and material resources, may help individuals cope with stress and self (Chu et al, 2010; Tian et al, 2013) and has been found to be a significant predictor of secondary education students' SWB and life satisfaction (Poudel et al, 2020). Moreover, students with learning difficulties have been shown to be more sensitive to the supportiveness of adults at school than their peers (Lombardi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%